Synergy between essential oil components and antibiotics: a review - Langeveld, W. T.; Veldhuizen, E. J.; Burt, S. A.
With the increase in antibiotic-resistant bacteria and the lack of new antibiotics being brought onto the market, alternative strategies need to be found to cope with infections resulting from drug-resistant bacteria. A possible solution may be to combine existing antibiotics with phytochemicals to enhance the efficacy of antibiotics. A group of phytochemicals that is said to have such effects, according to in vitro studies, is essential oils (EOs)and their components. Amongst others, EOs containing carvacrol, cinnamaldehyde, cinnamic acid, eugenol and thymol can have a synergistic effect in combination with antibiotics. Several modes of action have been put forward by which antibiotics and the essential oil components may act synergistically, such as by affecting multiple targets; by physicochemical interactions and inhibiting antibacterial-resistance mechanisms. Many reported assays show additivity or moderate synergism, indicating that EOs may offer possibilities for reducing antibiotic use.
Keywords: ANTIBIOTIC; ESSENTIAL OIL; FIC; SYNERGY